Structure–property relationships of PCGTA welds of Inconel X750 in as-welded and post-weld heat treated conditions—A comparative study. (October 2015) - Ramkumar, K. Devendranath; Krishnan, S. Rahul; Ramanand, R.; Logesh, S.; Satyandas, Tushar; Ameer, Ajmal; Arivazhagan, N.
Graphical abstract: Highlights: Formation of migrated grain boundaries at the fusion zone of both ERNiCrCoMo-1 and ERNiCrMo-3 fillers. Improved weld strength after post-weld heat treatment. Higher impact toughness of the welds both in as-welded and PWHT conditions compared to parent metal. Structure–property relationships of the PCGTA weldments. Abstract: This article addresses the weldability, microstructure and mechanical properties of the multi-pass pulsed current gas tungsten arc welding (PCGTAW) of Inconel X750. PCGTA welding was accomplished using two fillers, namely ERNiCrCoMo-1 and ERNiCrMo-3. Interfacial and weld microstructures were characterized using optical and scanning electron microscopy techniques. Migrated grain boundaries (MGBs) were dominating at the fusion zone of both the weldments. Post-weld heat treatment (PWHT) was carried out on the weldments at 705 °C for 22 h and air cooled to assess the microstructural changes and its impact on the mechanical properties. Tensile studies corroborated that all the tensile failures occurred at the fusion zone for both the as-welded and the PWHT samples. Fascinatingly, the weldments after subjected to PWHT resulted in improved tensile strength and the joint efficiency of ERNiCrCoMo-1 and ERNiCrMo-3 weldments improved to 82.2% and 72.5%. However, ERNiCrMo-3 weldments exhibited better impact toughness than ERNiCrCoMo-1 weldments. The structure–property relationships of the weldments are also discussed in the present investigation.